Between the alienation of the good teacher and the outsourcing of education - ALONSO-SAINZ, Tania; SÁNCHEZ-ROJO, Alberto; GIL CANTERO, Fernando (Utopía y Praxis Latinoamericana, 2021)
The aim of this article is to get closer to a better definition of teacher identity beyond the discourse of competences. We start from the hypothesis that all the characteristics of the teacher are put into play in their professional practice. Our hermeneutical analyzes have concluded that public discourses neglect the debate on the good teacher, and that this occurs to the extent that external educational aims acquire more prominence tan intrinsic education aims. For this reason, actions are proposed in order to enhance the importance of goods in a more personal teacher identity conceptualization.